Efektivitas Revitalisasi Kawasan dalam Meningkatkan Aktivitas Perekonomian Usaha Mikro Kecil dan Menengah (UMKM) di Pahlawan Street Center (PSC) Kota Madiun - Cloudia Winery Aprida Jury; Deby Febriyan Eprilianto; Muhammad Farid Ma’ruf; Melda Fadiyah Hidayat (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the effectiveness of the revitalization of the Pahlawan Street Center (PSC) area in Madiun City in increasing the economic activity of MSMEs. PSC revitalization is an effort by the local government to organize business areas and public spaces while simultaneously encouraging local economic empowerment through the provision of facilities and guidance for MSMEs. The study used a descriptive qualitative approach, located in the PSC area of Madiun City. Informants were determined through purposive sampling involving the Madiun City Manpower and Legal Aid Office (DISNAKER-KUM), MSME administrators and actors, and PSC tourists. The results show that the PSC revitalization improves the physical quality of the area, resulting in increased visits. However, MSMEs' understanding of the goals of economic and social strengthening remains uneven. The program's targets are deemed appropriate, but coaching, digital marketing, and shopping visit patterns have not optimally reached all MSMEs. Physical arrangements are running on time, while non-physical coaching is inconsistent. Physical achievements have been seen, but the increase in MSME capacity, the stability of shopping visits, and the strengthening of the PSC image are not optimal. Overall, the PSC revitalization has not fully encouraged increased local economic activity because the strengthening of production, marketing, and consumption is not evenly distributed. Therefore, more structured non-physical interventions are needed to optimally achieve economic and social goals.